Marx's Inferno : The Political Theory of Capital - Roberts, William Clare (Book collections on Project MUSE., 2016)
Marx's Inferno reconstructs the major arguments of Karl Marx's Capital and inaugurates a completely new reading of a seminal classic. Rather than simply a critique of classical political economy, William Roberts argues that Capital was primarily a careful engagement with the motives and aims of the workers' movement. Understood in this light, Capital emerges as a profound work of political theory. Placing Marx against the background of nineteenth-century socialism, Roberts shows how Capital was ingeniously modeled on Dante's Inferno, and how Marx, playing the role of Virgil for the proletariat, introduced partisans of workers' emancipation to the secret depths of the modern "social Hell." In this manner, Marx revised republican ideas of freedom in response to the rise of capitalism.Combining research on Marx's interlocutors, textual scholarship, and forays into recent debates, Roberts traces the continuities linking Marx's theory of capitalism to the tradition of republican political thought. He immerses the reader in socialist debates about the nature of commerce, the experience of labor, the power of bosses and managers, and the possibilities of political organization. Roberts rescues those debates from the past, and shows how they speak to ever-renewed concerns about political life in today's world.